(untitled) (Bangladesh Journal of Animal Science, 2023)
Nutritional evaluation of feed ingredients is important for potential use in feed rations. It is very important to determine not only the nutrient content and quality of feeds but also their digestibility prior to adding in the ration. This study was undertaken to assess the potential nutritive value of selected shade-dried herbs of moringa, pineapple waste, and plantain through in situ degradation and in vitro gas production techniques. The study compared 4 treatments, namely moringa (MH), pineapple waste (PwH), plantain (PH) herbs, and a combination of three of them with a ratio of 1:1:1 (MxH). The rumen dry matter (DM) and crude protein (CP) degradability kinetics were analyzed by using the nylon bags (in situ) procedure and the organic matter digestibility and fermentation characteristics were analyzed by in vitro gas production technique. The results of the in situ study revealed that the ruminal dry matter disappearance differed significantly (P<0.001) among herbs at all incubation periods whereas the PH had the greatest disappearance and PwH had the lowest among all herbs. Significantly (P<0.05) the highest potential and effective degradability of dry matter were found in PH and the lowest in PwH among herbs. The ruminal CP disappearance differed significantly (p<0.05) among herbs at all incubation periods. The MH had the greatest CP disappearance whereas PwH had the lowest. Significantly (P<0.05) the highest potential and effective degradability of CP were found in MH and MxH, respectively, and the lowest in PwH among herbs. The results of the in vitro study revealed that cumulative gas production was increased with increasing the periods of incubation for all herbs. Significantly (P<0.05) the highest gas production was found in PH and MH among all herbs at 48h of incubation. The organic matter digestibility and metabolizable energy were found significantly (P<0.05) higher in MH & PH and lower in PwH. Short-chain fatty acids were also significantly (P<0.05) higher in MH & PH and lower in PwH among herbs. It may be concluded that both plantain and moringa herbs showed better potential and effective degradability and also higher organic matter digestibility and metabolizable energy comparable to pineapple waste herbs. Bangladesh Journal of Animal Science 52 (3): 88-98.